Synthesis and characterization of chitosan/zinc oxide nanoparticles for antibacterial activity - Nurul Amira, Ahmad Yusof (2020)
Metal oxide nanoparticles possess unique physical and chemical characteristics linked to their nanoscale size. Moreover, the metal oxide nanoparticles have an excellent antibacterial activity which could be used as an effective antibacterial agent. The aim of this study is to characterize and determine the antibacterial properties of the chitosan/ZnO nanoparticles against Gram-positive and Gram-negative bacteria, and the effect of chitosan/ZnO nanoparticles incorporated with hydrogel film on antibacterial properties. Considering that, nanoparticles of zinc oxide (ZnO) has been synthesized using zinc nitrate salt, sodium hydroxide by a microwave-assisted method. The operating parameter such as a stabilizer (chitosan), power heating (400 W, 600 W and 800 W) and time heating (4 min, 6 min and 8 min) play an important role in the synthesised of chitosan/ZnO nanoparticles. The presence of chitosan prevented the nanoparticles from agglomeration by producing a milky solution of chitosan/ZnO nanoparticles without any suspensions. Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) were used as a test microorganism. Uv-vis spectrophotometer indicated the presence of the chitosan/ZnO by a single peak at 360 nm. The presence of a new peak at around 427 cm-1 in the FTIR spectrum confirmed the existence of the ZnO phase. XRD patterns show that the chitosan/ZnO nanoparticles materials are good crystallinity and completely matched the hexagonal-wurtzite structure. FESEM revealed that chitosan/ZnO nanoparticles were uniformly distributed with the mean value of size is 70 nm and spherical shape. The effect of power and time heating on the size of the chitosan/ZnO nanoparticles can be shown by a nanoparticles size distribution with the average of 30 to 90 nm. The increasing power and heating time resulted in the increasing of the size due to the nucleation of nanoparticles. Surface zeta potential was negative for all the nanoparticles and varied from -29.6 to -20.9 mV. Chitosan/ZnO nanoparticles resulted in higher inactivation of S. aureus compared to E.coli. The results showed that chitosan/ZnO nanoparticles have displayed an antibacterial inhibition zone against S. aureus and E.coli which 16.0 and 13.4 mm, respectively. The chitosan/ZnO nanoparticles displayed a same antibacterial effect of S. aureus compared to E. coli when tested using growth curve analysis. The occurrence of chitosan/ZnO nanoparticles in hydrogel film detected at 522 cm-1 of absorption spectra. The presence of chitosan/ZnO nanoparticles in hydrogel film displayed a rough surface of hydrogel film. Hydrogel film incorporated with chitosan/ZnO nanoparticles showed effective inactivation effect towards S. aureus compared to E.coli. The more prominent and good zone of inhibition with size 25.0 mm was seen on the S. aureus bacteria. Overall, this study has successfully determined the optimum operating parameter for the synthesized of the chitosan/ZnO nanoparticles.